Pengaruh Lingkungan Kerja, Pengawasan Kerja dan Motivasi Kerja terhadap Disiplin Kerja Karyawan PT. Bandeng Juwana Group Semarang - Puspita Sari; Kis Indriyaningrum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research examines the influence of the work environment, work supervision and work motivation on work discipline. This research was conducted at PT. Bandeng Juwana Group Semarang.The sampling method uses non-probability sampling techniques with the research period from June - September 2023. The relationship or influence between variables is explained using the multiple regression analysis method.The research results show that the work environment, work supervision and work motivation have a positive significant effect on work discipline.